Loss of SIRT2 leads to axonal degeneration and locomotor disability associated with redox and energy imbalance (2017)
ABSTRACT: Sirtuin 2 (SIRT2) is a member of a family of NAD+ -dependent histone deacetylases (HDAC) that play diverse roles in cellular metabolism and especially for aging process. SIRT2 is located in the nucleus, cytoplasm, and mitochondria, is highly expressed in the central nervous system (CNS), and has been reported to regulate a variety of processes including oxidative stress, genome integrity, and myelination. However, little is known about the role of SIRT2 in the nervous system specifically during aging. Here, we show that middle-aged, 13-month-old mice lacking SIRT2 exhibit locomotor dysfunction due to axonal degeneration, which was not present in young SIRT2 mice. In addition, these Sirt2 / mice exhibit mitochondrial depletion resulting in energy failure, and redox dyshomeostasis. Our results provide a novel link between SIRT2 and physiological aging impacting the axonal compartment of the central nervous system, while supporting a major role for SIRT2 in orchestrating its metabolic regulation. This underscores the value of SIRT2 as a therapeutic target in the most prevalent neurodegenerative diseases that undergo with axonal degeneration associated with redox and energetic dyshomeostasis. Key words: aging; axonal degeneration; mitochondria; redox dyshomeostasis; sirtuin.